The Federal Aviation Administration's approach for determining future air traffic controller staffing needs (Special report (National Research Council (U.S.). Transportation Research Board), 2014)
"TRB Special Report 314, The Federal Aviation Administration's Approach for Determining Future Air Traffic Controller Staffing Needs, examines the methods used by the Federal Aviation Administration (FAA) to estimate how many controllers are needed to staff its air traffic control facilities and FAA's processes for using these estimates to properly distribute controllers across facilities. According to the report, FAA's models for determining air traffic controller staffing needs are suitable for developing initial estimates of the number of controllers required at terminal areas and airport towers, but the models used for the centers controlling aircraft en route between airports can be improved. In addition, as a matter of priority, the FAA should collaborate with the National Air Traffic Controllers Association to develop and implement an enhanced tool for all facilities that is capable of creating efficient controller work schedules that incorporate fatigue mitigation strategies. The report recommends that the FAA analyze a wide range of data, such as accident and incident reports and voluntary reports by controllers, to identify relationships between staffing and safety. In addition, the controller workforce should be involved in staffing decisions, particularly as knowledge emerges about relevant safety issues. The report also says that FAA should ensure that staffing continue to be appropriate as FAA implements the new air traffic operations environment associated with the Next Generation Transportation System, a modernization initiative to shift air traffic management from ground-based radar to a satellite system"--Provided by publisher.